Selective Mineralocorticoid Receptor Cofactor Modulation as Molecular Basis for Finerenone's Antifibrotic Activity. Issue 4 (April 2018) - Grune, Jana; Beyhoff, Niklas; Smeir, Elia; Chudek, Remigiusz; Blumrich, Annelie; Ban, Zsofia; Brix, Sarah; Betz, Iris R.; Schupp, Michael; Foryst-Ludwig, Anna; Klopfleisch, Robert; Stawowy, Philipp; et al.
Abstract : Mineralocorticoid receptor antagonists (MRAs) reduce morbidity and mortality in chronic heart failure. Novel nonsteroidal MRAs are currently developed and need to be pharmacologically characterized in comparison to classical steroidal MRAs. A mouse model of cardiac fibrosis induced by short-term isoproterenol injection was used to compare the nonsteroidal MRA finerenone and the steroidal MRA eplerenone in equi-efficient systemic MR blocking dosages. Molecular mechanisms were studied in MR-expressing H9C2/MR+ cardiomyocytes and in MR transcriptional cofactor binding assays. Both MRAs significantly inhibited an isoproterenol-mediated increase of left ventricular mass. Isoproterenol-induced cardiac fibrosis and macrophage invasion were potently blocked by finerenone, whereas eplerenone had no significant effect. Speckle tracking echocardiography revealed a significant improvement of global longitudinal peak strain by finerenone, an effect less prominent with eplerenone. Antifibrotic actions of finerenone were accompanied by a significant inhibition of profibrotic cardiac TNX ( tenascin-X ) expression, a regulation absent with eplerenone. Finally, we show a higher potency/efficacy and inverse agonism of finerenone versus eplerenone in MR transcriptional cofactor binding assays indicating differential MR cofactor modulation by steroidal and nonsteroidal MRAs. This study demonstrates that the nonsteroidal MRA finerenone potently prevents cardiac fibrosis and improves strain parameters in mice. Cardiac antifibrotic actions of finerenone may result from the inhibition of profibrotic TNX gene expression mediated by differential MR cofactor binding. Selective MR cofactor modulation provides a molecular basis for distinct (pre)-clinical actions of nonsteroidal and steroidal MRAs. Abstract : Supplemental Digital Content is available in the text.